A CONSTITUENT OF CHAROTAR UNIVERSITY OF SCIENCE AND TECHNOLOGY - Vageriya, Vipin (European Scientific Journal, ESJ, 2014)
“A study to assess the effectiveness of Structured teaching Program on knowledge about the prevention of lead poisoning among the mothers of toddlers in selected rural areas of Hassan in Karnataka”.